2012
DOI: 10.1159/000345077
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Stroke Centers and the ‘Weekend Effect’: The SPOTRIAS Experience

Abstract: Background and Purpose: Previous studies have found mortality among ischemic stroke patients to be higher on weekends. We sought to evaluate whether weekend admission was associated with worse outcomes in a large comprehensive stroke center (CSC) cohort. Methods: Consecutive ischemic stroke patients presenting within 6 h of symptom onset were identified using the 8 CSC SPOTRIAS (Specialized Programs of Translational Research in Acute Stroke) database. Patients who received intra-arterial therapy or who were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 38 publications
5
66
0
Order By: Relevance
“…Some have found evidence for reduced quality of care for patients admitted on weekends 18 , but the evidence for differences in mortality between weekend and weekday admissions has been mixed. 19,20,21 These differences might be explained by differences in how stroke care services are organised 21 , and there is evidence that low nurse staffing levels on stroke units are associated with higher mortality at weekends. 22 The limitation of much of the previous literature on the "weekend effect" is that it has typically been based on comparisons of weekends versus weekdays, or regular versus off-hours, without taking into account variation that might occur across both day of the week and time of day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have found evidence for reduced quality of care for patients admitted on weekends 18 , but the evidence for differences in mortality between weekend and weekday admissions has been mixed. 19,20,21 These differences might be explained by differences in how stroke care services are organised 21 , and there is evidence that low nurse staffing levels on stroke units are associated with higher mortality at weekends. 22 The limitation of much of the previous literature on the "weekend effect" is that it has typically been based on comparisons of weekends versus weekdays, or regular versus off-hours, without taking into account variation that might occur across both day of the week and time of day.…”
Section: Discussionmentioning
confidence: 99%
“…The study would have been strengthened by including more outcome measures, particularly of measures important after stroke, such as disability and quality of life. However, most of the process measures have a strong empirical rationale from good quality randomised controlled trial evidence 29,20 , and longer term outcomes data are not currently available in SSNAP. The evidence for stroke therapy interventions is generally weaker than other aspects of acute care but are widely recognised in clinical guidelines to be an essential element of acute stroke care 10 .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] For example, comprehensive stroke centers, staffed by super-specialized care providers, have been shown to provide improved outcomes for patients presenting for treatment of acute ischemic stroke. 8,9 Similarly, improved outcomes among certain high-volume hospitals that perform bariatric surgery have led the Centers for Medicare and Medicaid Services (CMS) to designate some institutions as "centers of excellence." 10,11 For most surgical specialties, however, formal identification of super-specialization at the hospital level is rarely formalized or publically designated.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have not found differences in short-term mortality when restricting to patients admitted to specialized stroke centers, indicating that organizational factors [25][26][27][28] may be important in understanding the weekend-or off-hours effect. Across patient populations, the body of scientific work supporting the existence of a weekend-or off-hour-effect is substantial.…”
Section: Days Case-fatalitymentioning
confidence: 93%